(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This article delves into the evolving landscape of healthcare professions, specifically examining the integration of medical nursing with laboratory technology. Traditionally distinct disciplines, the merging of these roles holds promise for streamlining health care delivery and optimizing patient outcomes. Through an exploration of the responsibilities, training requirements, and potential benefits of nurses assuming lab technician duties, this article aims to shed light on the synergies between these professions. By bridging the gap between bedside care and diagnostic testing, nurses equipped with laboratory skills can contribute to more comprehensive patient care strategies. Furthermore, this integration has the potential to alleviate staffing shortages and enhance efficiency within healthcare settings. Drawing on current research and practical examples, this article underscores the importance of interdisciplinary collaboration and skill diversification in modern healthcare practice.